Effects of Maternal Stress on Measures of Anxiety and Fearfulness in Different Strains of Laying Hens - Peixoto, Mariana R. L. V.; Karrow, Niel A.; Newman, Amy; Widowski, Tina M. (Frontiers in Veterinary Science, 2020)
Maternal stress can affect the offspring of birds, possibly due to hormone deposition in the egg. Additionally, phenotypic diversity resulting from domestication and selection for productivity has created a variety of poultry lines that may cope with stress differently. In this study, we investigated the effects of maternal stress on the behaviour of different strains of laying hens and the role of corticosterone as its mediator. For this, fertilized eggs of 5 genetic lines — 2 brown (Brown 1 & 2), 2 white (White 1 & 2) and 1 pure line White Leghorn — were reared identically as 4 flocks of 27 birds (24F: 3M) per strain. Each strain was equally separated into 2 groups: Maternal Stress (“MS”), where hens were subjected to a series of daily acute psychological stressors for 8 days before egg collection, and “Control,” which received routine husbandry. Fertile eggs from both treatments were collected at 3 different ages forming different offspring groups that were treated as replicates in time; additional eggs from Control were injected either with corticosterone diluted in a vehicle solution (“CORT”) or just “Vehicle”. Eggs from each replicate were incubated, hatched, and offspring (N=1919) were brooded under identical conditions. To measure the effects of maternal stress on anxiety-like and fear behaviour, offspring were subjected to a social isolation test (SI) between 5 to 10 days of age, and a tonic immobility test (TI) at 9 weeks of age. Compared to Control, MS decreased the number of distress vocalizations emitted by White 2 in SI. No effects of MS were observed in TI, and no effects of CORT were observed in any tests. Overall, brown lines vocalized more in SI and remained in TI for a longer duration than white strains, suggesting genetic differences in fear behaviour. Females vocalized more than males in TI and showed a trend towards significance for the same trait in SI. Overall, results suggest that the effects of maternal stress on fearfulness are not directly mediated by corticosterone. Moreover, it highlights behavioural differences across various strains of laying hens, suggesting that fear response is highly dependent on genotype.